Rationality Analysis of Antibiotic Use in Chronic Kidney Disease Patients at Dr. R. Sosodoro Djatikoesoemo Regional HospitalUsing the Gyssens Method - Dian Aisyah Aprilina; Titi Agni Hutahaen; Ainu Zuhriyah; Sabilah Sebil Noer (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Chronic kidney disease (CKD) requires special attention in antibiotic therapy due to pharmacokinetic changes that can affect drug concentration and efficacy. Inappropriate antibiotic selection or dosing may increase toxicity risk and further impair renal function. This study aimed to analyze the rationality of antibiotic use in CKD patients in the internal medicine ward of Dr. R. Sosodoro Djatikoesoemo Regional Hospital, Bojonegoro. A retrospective design was used, analyzing patient medical records from July to December 2024. The rationality of antibiotic use was assessed using the Gyssens method, which evaluates the appropriateness of indication, dosage, interval, duration, and antibiotic selection. Among 91 patients, the largest age group was 45–55 years (26.37%), with a hospital stay of 1–3 days (51.65%). The most frequently used antibiotics were ceftriaxone (43.96%) and cefepime (32.97%). The Gyssens analysis showed that 63.74% of antibiotic use was rational (category 0), while 36.26% was irrational, with the most common issue being category IVd (availability of a narrower-spectrum alternative) at 37.36%. Although most antibiotic use complied with clinical guidelines, there remains a need for improvement in selecting antibiotics with a more appropriate spectrum. Strengthening antibiotic stewardship programs is expected to improve therapeutic outcomes, minimize toxicity risks, and prevent antimicrobial resistance in hospital settings.